2017
DOI: 10.7287/peerj.preprints.2709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Nf-ҝb prevents trauma-induced heterotopic ossification in rat model

Abstract: Background. To find a better prophylactic regimen, the pathogenesis of acquired heterotopic ossification (AHO) must be more understood. To date, AHO formation is largely thought to be related to inflammation, which is activated by trauma, resulting in AHO by up-regulation of pro-osteogenic genes. Methods. Brain-traumatic/burn/tenotomy model is firstly used in experiment. At first, 44 rats were randomly divided into two groups: E group and C group. Two rats in every group were euthanized during second, third, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…However, after SRT1720 HCI treatment, acetylated NFκB p65 expression was largely weakened, paralleled by the reduced macrophage and mast cell presence and consistent with the assumption that the immunomodulatory effects of SIRT1 may be due to altered NFκB signaling. In accordance with this finding, prolonged NFκB pathway activation was found in monocytes and macrophages from FOP patients ( 16 ), and pharmacological inhibition of canonical NFκB signaling also abrogated HO in a rat brain-traumatic/burn/tenotomy model ( 54 ). Altogether, we showed that impaired SIRT1/NFκB signaling was responsible for aberrant immunity during HO development.…”
Section: Discussionsupporting
confidence: 70%
“…However, after SRT1720 HCI treatment, acetylated NFκB p65 expression was largely weakened, paralleled by the reduced macrophage and mast cell presence and consistent with the assumption that the immunomodulatory effects of SIRT1 may be due to altered NFκB signaling. In accordance with this finding, prolonged NFκB pathway activation was found in monocytes and macrophages from FOP patients ( 16 ), and pharmacological inhibition of canonical NFκB signaling also abrogated HO in a rat brain-traumatic/burn/tenotomy model ( 54 ). Altogether, we showed that impaired SIRT1/NFκB signaling was responsible for aberrant immunity during HO development.…”
Section: Discussionsupporting
confidence: 70%
“…The results demonstrated that palovarotene reversed osteogenic differentiation of BMSCs under the influence of IL‐1β. According to our previous findings, the NF‐κB signalling pathway may be involved in the osteogenic differentiation of BMSCs 16 . To verify this hypothesis; we performed western blotting and immunofluorescence assays.…”
Section: Resultsmentioning
confidence: 85%
“…According to our previous findings, the NF-κB signalling pathway may be involved in the osteogenic differentiation of BMSCs. 16 To verify this hypothesis; we performed western blotting and immunofluorescence assays. We focused on the core molecule of the NF-κB signalling pathway, p65 and the immunofluorescence results The animals were divided into six groups as follows: control 1 and 2, model 1 and 2, and palovarotene and PDTC.…”
Section: Nf-κb Signalling Pathway May Play An Important Role In Il-1β...mentioning
confidence: 99%